PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SD NEGERI 007 TANJUNG PENYEMBAL - Hendra adinata adinata; Munjiatun '; Mahmud Alpusari Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract. This Background research internal issue is result learn IPA class student of III SDN 007 Tanjung Penyembal still pertained to lower. Hence from that/conduct by research by using model study of type co-operative of STAD. Form this research is research of class action. this Research Subjek is class student of III SDN 007 Tanjung Penyembal. Of collected data analysis in the form of result of and observation of tes result of learning student. Of data analysis which in collecting the make-up of complete percentage of klasikal of data early, cycle of I, and cycle of II natural  improvement. This research is conducte by at even semester in the year teaching 2013-2014 with amount of student 25 student people which consist of 7 woman student people and 18 student people of laki-laki. Analyse data which collecting the make-up of percentage of activity learn and student activity also experience of the make-up of from meeting of I and meeting to II Keyword : Model Study Of Co-Operative Type of STAD, Result of Learning IPA